Pola Integrasi Kurikulum di Pondok Pesantren Al Inaayah Gunung Sindur Bogor - Hayaturrohman; Bahri, Saiful; Rahman, M. Abd.; Mulyanto, Agus (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Islamic boarding schools, known as pesantren, have been established long before the nation gained independence and their existence continues to be prominent. Equipped with specific components, pesantren remains a sought-after educational institution among many Indonesian muslims. Regardless of their diverse forms, pesantren in Indonesia share fundamental elements and exhibit autonomy in educational management based on their unique characteristics. The curriculum within pesantren allows these institutions to persist and evolve with the changing times. This research aims to unravel the pattern of curriculum integration implemented by Pesantren Al Inaayah, which plays a pivotal role in its sustained relevance and positioning as an alternative educational choice for parents entrusting their children's education. The methodology employed in this study is rooted in various literary theories, complemented by on-site observations to assess the real conditions within the pesantren. To enhance data accuracy, the researcher conducted interviews with pesantren administrators, including caretakers, the director of tarbiyatul mu’allimin al Islamiyah at Al Inaayah, the teaching council, and several students, employing both structured and unstructured interview formats. Additionally, the researcher documented information related to Pesantren Al Inaayah in Gunungsindur Bogor. The findings indicate that Pesantren Al Inaayah successfully integrates its curriculum, instilling confidence in the institution's ability to meet societal expectations in nurturing the anticipated generation of the nation.